A Comparison of Two Sodium Citrate Concentrations in Two Evacuated Blood Collection Systems for Prothrombin Time and ISI Determination - van den Besselaar, A. M. H. P.; Chantarangkul, V.; Tripodi, A. (Thrombosis and Haemostasis, 2000)
The prothrombin time is usually measured in citrated plasma. The W.H.O. recommended concentration of sodium citrate for blood collection for laboratory control of oral anticoagulant therapy is 0.109 M. Some evacuated blood collection systems include 0.105 M sodium citrate. The purpose of the present study was to establish the difference in ISI calibration between 0.109 and 0.105 M citrate, using 7 types of thromboplastin and various types of instrumentation. The two citrate concentrations were provided in both evacuated siliconised glass tubes and in evacuated polyethylene terephtalate (PET) tubes. The ISI difference between the two citrate concentrations was 5.4% for one system but not greater than 3% for all other systems when blood samples were collected with either siliconized glass or PET tubes. Most of the ISI differences between the two citrate concentrations were not significant at the 5% level. It is concluded that the ISI differences between 0.105 M and 0.109 M citrate are not of practical importance. In contrast, ISI differences between siliconised glass and PET tubes, using either 0.105 or 0.109 M citrate, were significant (p <0.05) for most thromboplastin systems and amounted to 7%. ISI interchange between these glass and PET tubes could induce INR differences amounting to 14%, which could affect clinical dosage of oral anticoagulants.
Keywords: Prothrombin time; ISI; oral anticoagulant control; blood collection; citrate